2011
DOI: 10.1029/2011jd015773
|View full text |Cite
|
Sign up to set email alerts
|

Properties of air mass mixing and humidity in the subtropics from measurements of the D/H isotope ratio of water vapor at the Mauna Loa Observatory

Abstract: [1] Water vapor in the subtropical troposphere plays an important role in the radiative balance, the distribution of precipitation, and the chemistry of the Earth's atmosphere. Measurements of the water vapor mixing ratio paired with stable isotope ratios provide unique information on transport processes and moisture sources that is not available with mixing ratio data alone. Measurements of the D/H isotope ratio of water vapor from Mauna Loa Observatory over 4 weeks in October-November 2008 were used to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
154
0
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(165 citation statements)
references
References 72 publications
9
154
0
2
Order By: Relevance
“…This suggests that a considerable fraction of the water content is originating from processes other than slow ascent and dehydration of boundary layer air. A model based on the method described by Noone et al (2011) that describes mixing of moist air typical of the MBL (H 2 O = 22 900 ppmv, δD = −75.6 ‰) and dry air from the upper troposphere (UT; H 2 O = 1100 ppmv, δD = −385 ‰) excellently fits our observations (solid line (4) in Fig. 11).…”
Section: Atmossupporting
confidence: 67%
“…This suggests that a considerable fraction of the water content is originating from processes other than slow ascent and dehydration of boundary layer air. A model based on the method described by Noone et al (2011) that describes mixing of moist air typical of the MBL (H 2 O = 22 900 ppmv, δD = −75.6 ‰) and dry air from the upper troposphere (UT; H 2 O = 1100 ppmv, δD = −385 ‰) excellently fits our observations (solid line (4) in Fig. 11).…”
Section: Atmossupporting
confidence: 67%
“…Nor was it consistent with modified distillation expected during moist convection (refer to Figure 5). Instead, large variations along the x axis in the isotopic mixing diagram (Figure 10) point to a probable role for large-scale transport, which previous studies have argued controls the isotopic composition of the free troposphere near Hawaii to first order [Galewsky et al, 2007;Noone et al, 2011;Hurley et al, 2012].…”
Section: Processes Influencing the Moisture Properties At Cbl Topmentioning
confidence: 87%
“…The trade wind temperature inversion typically limits convective activity on Hawaii's east side [Price and Pales, 1963;Garrett, 1980]; however, Noone et al [2011] observed strong convective activity when regional winds shifted to southwesterly. Upper air radiosondes Figure 13.…”
Section: Processes Influencing the Moisture Properties At Cbl Topmentioning
confidence: 97%
See 2 more Smart Citations